2022
DOI: 10.1007/s40258-022-00785-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Efficiency of Health Systems: A Systematic Review of the Literature

Abstract: Background Efficiency refers the use of resources in ways that optimise desired outcomes. Health system efficiency is a priority concern for policy makers globally as countries aim to achieve universal health coverage, and face the additional challenge of an aging population. Efficiency analysis in the health sector has typically focused on the efficiency of healthcare facilities (hospitals, primary healthcare facilities), with few studies focusing on system level (national or sub-national) efficiency. We carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…It can be defined as the average number of years that a person at a certain age would live in full health, i.e., in absence of disease or disability [28]. Life expectancy and healthadjusted life expectancy are the most commonly used outputs in system efficiency studies [9,25] since they are a 'reasonable' objective for the institutional framework for which the analysis is undertaken [29]. However, the main goal of health systems is not merely restricted to an increase in life expectancy, but also to an improvement in quality of life by tackling a range of health issues that do not necessarily result in death.…”
Section: Output Variablesmentioning
confidence: 99%
See 3 more Smart Citations
“…It can be defined as the average number of years that a person at a certain age would live in full health, i.e., in absence of disease or disability [28]. Life expectancy and healthadjusted life expectancy are the most commonly used outputs in system efficiency studies [9,25] since they are a 'reasonable' objective for the institutional framework for which the analysis is undertaken [29]. However, the main goal of health systems is not merely restricted to an increase in life expectancy, but also to an improvement in quality of life by tackling a range of health issues that do not necessarily result in death.…”
Section: Output Variablesmentioning
confidence: 99%
“…Given the absence of consensus, the current methodological choices must consider the objective of the analysis and the type and quality of the data used [8]. While health system outputs are often population health measures, health system inputs are often measured in the form of expenditures [1,9]. It is also essential to decide on the environmental variables to include, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have employed traditional methods such as data envelopment analysis (DEA) and stochastic frontier analysis (SFA) to assess resource efficiency [4,14,16]. Studies utilizing DEA have revealed significant variations in efficiency levels among hospitals, indicating potential area for improvement [6]. By identifying sources of inefficiency, healthcare providers and policymakers can implement targeted interventions to enhance resource utilization and streamline processes [17].…”
Section: Introductionmentioning
confidence: 99%